Powers and Functions of the DPD RI: Performance Evaluation for the 2019–2024 Term - Dhamar Kusuma; M. Nur Rofiq Addiansyah (Jurnal Pemerintahan dan Politik Lokal, 2026)
The Regional Representative Council is an upper house institution in the bicameral system, but its authority as a legislative institution is very limited and its existence is almost considered non-existent. This existential crisis has caused the Regional Representative Council to receive a lot of criticism as an institution that only spends the State budget because its functions and roles are considered unclear. This research aims to determine the performance of members of the Regional Representative Council of the Republic of Indonesia, Central Java Province amidst the limitations of their function and authority as an upper house institution in a bicameral system. In this research analysis, the researcher collected data using qualitative and quantitative methods where the researcher took data through a literature review in previous research and conducted direct interviews with members of the Regional Representative Council of the Republic of Indonesia, Central Java Province. This research contributes to introducing and understanding the performance of each committee of the Regional Representative Council of the Republic of Indonesia, Central Java Province amidst the limitations of its function as a legislatif institution. This study has limitations, including a focus on a single region, meaning the findings cannot be directly generalized, and a reliance on internal interviews, which may introduce reporter bias. For future research, a multi-province comparative study is recommended, employing a mixed-methods approach with public surveys and independent data.